Causative Organisms and Antimicrobial Sensitivity Pattern in Patients with Urinary Tract Infection : Antimicrobial Sensitivity Pattern with Urinary Tract Infection - Zaman, Mamoona; Ahmad, Shahan; Idrees, Nauman; Ahmad, Faryal; Naseer, Sana; Gul, Rabia (Pakistan Journal of Health Sciences, 2025)
Patterns of pathogens in urinary tract infection (UTI) and antibiotic sensitivity have been scarcely studied in the recent past in local settings. Hence, the study has been planned to address the knowledge gap arising from the non-availability of recent data. Objectives: To evaluate the causative organisms and antimicrobial sensitivity patterns in patients with urinary tract infections. Methods: This descriptive cross-sectional study was carried out at the Medicine Department of Khyber Teaching Hospital, Peshawar, during the period 1st July 2022 till 31st December 2022. Male and female patients aged 20 to 80 years with culture-proven urinary tract infections were enrolled. Pathogens isolated were noted their sensitivity to antibiotics was assessed. Data were analyzed using SPSS version 26.0. Results: The majority of study participants were aged more than 50 years (n=92, 51.4%). 109 patients (60.9%) were male, and 85 patients (47.5%) were diabetic. 89 patients (49.7%) were enrolled from the Outpatient Department. The most common pathogen was E coli, recorded in 48 patients (26.8%). Isolates in 154 (86.0%) out of 179 participants were susceptible to nitrofurantoin, followed by meropenem in 151 (84.3%). Conclusions: It was concluded that people of all ages can be affected by urinary tract infection. The most common bacterial cause of UTI is E coli. Nitrofurantoin and meropenem are the most effective antibiotics against uropathogens.